Sturgeon, Caviar, and Caviar Substitutes: From Production, Gastronomy, Nutrition, and Quality Change to Trade and Commercial Mimicry. Issue 4 (2nd October 2021) - Tavakoli, Samad; Luo, Yongkang; Regenstein, Joe M.; Daneshvar, Ehsan; Bhatnagar, Amit; Tan, Yuqing; Hong, Hui
Abstract: The demand for caviar has increased in recent years because of its high nutritional and commercial values. Consequently, the wild population of sturgeon has decreased. This has shifted the balance of supply of caviar from wild sturgeon to more from farmed fish. The development of aquaculture has resulted in many technical advances of sturgeon rearing. The same factors that encouraged sturgeon farming have also stimulated the search for alternative products optimizing wild-sourced caviar utilization and even created some new market opportunities. Caviar substitutes have been obtained from at least 38 fish species (other than sturgeon) and aquatic animals, e.g., sea urchin, sea cucumber and snails. Although, the emergence of products has not always been positive, as the sturgeon caviar market has been impacted by commercial mimicry, fraud, and mislabeling of caviar-substitutes. This review provides information about the global production and trade of sturgeon, caviar, and caviar substitutes. In addition, the physics, gastronomy, and the quality changes of caviar and caviar substitutes during different fish-harvesting steps are discussed. Moreover, information about commercial mimicry, fraud, and new methods to detect these criminal acts are considered.